Selecting the governance mode when offshoring knowledge-intensive activities. Issue 4 (October 2018) - Paz-Aparicio, Carmen; Muñoz-Bullón, Fernando; Sanchez-Bueno, Maria J.; Ricart, Joan E.
Abstract: The offshoring phenomenon has evolved in recent years, and can be understood from a threefold perspective: first, the evolution in the type of activity being offshored; second, the learning curve involving both the companies implementing offshoring and service providers; and third, the reasons for offshoring. This study proposes an empirical framework that will allow us to explore the interaction between the type of activity (specifically knowledge-intensive) and the drivers of the decision to select the most appropriate governance mode. Specifically, our results show that market-seeking drivers become the primary determinants prompting firms to offshore knowledge-intensive activities through a captive center. In contrast, the motivation to reduce costs moderates the decision to offshore knowledge-intensive activities by nurturing a preference for offshore outsourcing. The empirical evidence is supported by multi-country data from the Offshoring Research Network. Highlights: The evolution of the offshoring phenomenon comes from a threefold perspective. We propose an empirical model to understand the decision to offshore K-I activities. Market-seeking drivers are determinants for firms to captive offshore K-I activities. Cost drivers promote a preference for offshore outsourcing K-I activities. Empirical evidence is supported with the entire multi-country data from the ORN.